Mebde͗ ve Me͑ād: Kelam ilmi ve modern kozmoloji açısından evrenin başlangıcı ve sonu - BULGEN, MEHMET (My University, 2022)
Discussions about the beginning (mabda͗) and the end (ma͑ād) of the universe (͑ālam) have been among the subjects that the science of kalām has dealt with since the early times. Mutakallimūn, with the concepts and theories they developed, tried to prove that the universe had a beginning, as well as the possibility of it having an end. In the last century, the emergence of scientific cosmology, which studies the universe as a whole, has led to the development of scientific theories about the beginning and end of the universe. In this context, while the Big Bang Theory implies that the universe had a beginning, on the other hand, the Entropy Theory, developed on the basis of the second law of thermodynamics, brought the idea that the universe would come to an end. In the present study, it will be revealed how Islamic theologians (mutakallimūn) defended the idea that the universe had a beginning and an end, based on the concepts and theories valid in their own time, and then an evaluation of their views in terms of modern cosmology will be made. Given that one of the definitions of the science of kalām, which is widely shared both in the classical period and today, is a science that examines the universe in terms of origin (mabda͗) and end (ma͑ād), it is expected that this study will give an idea about how this distinctive aspect of kalām can be renewed today. The fact that mutakallimūn discussed the beginning and end of the universe with philosophical concepts and scientific theories in the past legitimizes the use of contemporary philosophical and scientific theories on this subject. In this respect, it is hoped that the article will contribute to updating the science of kalām.
Keywords: Sosyal ve Beşeri Bilimler; İlahiyat; Social Sciences and Humanities; Theology; Sanat ve Beşeri Bilimler (AHCI); Sanat ve Beşeri Bilimler; DİN; Arts & Humanities (AHCI); ARTS & HUMANITIES; RELIGION; Dini çalışmalar; Sosyal Bilimler ve Beşeri Bilimler; Religious Studies; Social Sciences & Humanities; Cosmology; Kalām; The Beginning (mabda͗); The End (ma͑ād); Universe (͑ālam); Kelam; Kozmoloji; Evren; Başlangıç (Mebdeʾ); Son (Meʿād)